DISCOVER-PHILIPPINES REGISTRY: DIABETES CARE AND COMPLICATIONS AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS IN THE PHILIPPINES – A PRELIMINARY REPORT - C. Fojas, Mia; Gonzales, Maria Lourdes Ella; Limpoco, Guia; Dampil, Allan Oliver (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION The DISCOVER Global Registry is an ongoing prospective observational database of patients with type 2 diabetes being managed by primary care physicians and specialists. This registry aims to collect real-world data on patient care in selected countries. In the Philippines, a similar survey on glycemic control and complications was last undertaken in 2008. METHODOLOGY A total of 518 patients were enrolled into the DISCOVER Registry from October 2018 to June 2019. Data were obtained through review of medical records: demographics (birth date, sex, educational status, health insurance), medical history (duration of diabetes, co-morbidities, therapies), physical measurements (weight, height, blood pressure), lifestyle (smoking, alcohol drinking), and laboratory tests. RESULTS The patient population was predominantly male (53.7%), at mean age 58 years, a BMI of 28.3 kg/m2 , retired (36.7%), and had a higher level of education (80.4%). Mean diabetes duration was 6.3 years. Mean HbA1c was 7.4%, with 56.1% achieving the target A1c <7%. History of hypertension and dyslipidemia were both 62.5%. The most common complications were nephropathy (7.1%), but mean eGFR was 84.7 mL/min/1.73 m2 , followed by retinopathy (4.8%), stroke (3.5%) and diabetic foot infections (2.5%). Treatment with Metformin as monotherapy was highest (30.3%), followed by a combination of metformin and dipeptidyl peptidase-4 inhibitor (24.0%). CONCLUSION These results suggest that over half of patients in the Philippines are achieving adequate glucose control, with a small proportion having associated complications. Future analyses, with inclusion of more patients from across the Philippines, may provide assessment of the generalisability of these findings.